Nonlinear buckling finite element analysis of stiffened B-Al plates - Gunay, Ezgi; Aygun, Cevdet; Yildiz, Yunus Onur (Elsevier Science Bv, 2014)
Nonlinear buckling behavior of stiffened composite B-Al plates was analyzed by means of finite element analysis (FEA) method. In the method, the composite material was taken as B matrix into which Al fibers were embedded in different configurations. The laminated B-Al material in the form of rectangular plates was subjected to lateral compressive loading. It is observed that stiffeners have significant effect on the buckling behavior of plates under compressive loading and for various geometrical configurations. The stiffeners used in the modeling are one-sided and have rectangular cross-sections. It is found that there are physically important loading intervals and the critical buckling modes make transitions back and forth between stable and unstable states. Bifurcation buckling regions resulting from various configurations of fiber orientations and different plate aspect ratios are determined. The whole analysis is performed by using ANSYS finite element computations. Only the buckling patterns of stiffened plate configurations under simply supported boundary conditions are studied. Distributions of compressive stresses (sigma(x)) vs in-plane contractions (u) and compressive stresses (sigma(x)) vs out-of plane deflections (delta) are obtained. Nonlinear analysis of the C2 fiber configuration yields the safest critical buckling stress amongst C1, C2, C3 and C4 configurations. It is concluded that FEA method for the nonlinear buckling analysis generates accurate results.
Keywords: nonlinear buckling; stiffener; composite plate; bifurcation; FEM modeling